2020
DOI: 10.1177/1039856220970057
|View full text |Cite
|
Sign up to set email alerts
|

Association between sources of stress and depressive mood in Korean adults

Abstract: Objective: The present study investigated the association between different sources of stress and depressive mood in Korean adults. Methods: A total of 4464 adults who completed the 2018 Korean National Health and Nutrition Examination Survey were included in the analysis. Data included sources of stress, depressive mood assessed by the nine-item Patient Health Questionnaire, sociodemographic characteristics, and health-related habits. Multiple logistic regression models were applied to calculate the odds rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In other words, individuals with greater concerns about their health may be sensitive to depression during a serious situation such as the COVID-19 pandemic ( 52 , 53 ). The intensity of worried thoughts and health concerns about COVID-19 were found to be positively correlated with anxiety and depression, and negatively with SLP ( 54 ). In terms of the findings revealed in this study, Lee ( 55 ) also found that HC is positively related to fear and anxiety and not related to information seeking.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, individuals with greater concerns about their health may be sensitive to depression during a serious situation such as the COVID-19 pandemic ( 52 , 53 ). The intensity of worried thoughts and health concerns about COVID-19 were found to be positively correlated with anxiety and depression, and negatively with SLP ( 54 ). In terms of the findings revealed in this study, Lee ( 55 ) also found that HC is positively related to fear and anxiety and not related to information seeking.…”
Section: Discussionmentioning
confidence: 99%